Pengaruh Pemberian Kaldu Ayam dalam Olahan Makanan terhadap Peningkatan BB pada Anak Usia 1-3 Tahun - Nafisatul Aini; R. Maria Veronika (Jurnal MID-Z (MIDWIFERI ZIGOT), 2025)
One aspect of health that is a concern in Indonesia's Efforts to Realize the SDGs is the nutritional condition of toddlers. The target to be achieved by 2030 includes the elimination of all forms of malnutrition. Several indicators used to measure this achievement include the prevalence of underweight toddlers, the prevalence of stunting (height below the age standard, both short and very short categories), and the prevalence of malnutrition in toddlers (Ministry of PPN/Bappenas, 2017). This study is intended to examine the effect of providing chicken broth in processed foods on increasing the weight of children aged 1-3 years at the Kemuningsari Kidul Health Center. The research design model chosen is a quasi-experimental design with a pre-test-post test design. A difference test was carried out for a comparison of the weight of children aged 1-3 years before and after the intervention was analyzed using the Paired t-Test. The sampling technique used was the total sample. A total of 63 children aged 1-3 years who were registered as participants and actively attended the integrated health post in the last 3 months met the inclusion criteria in sampling.